Usulan Penataan Ulang Tata Letak Fasilitas Dengan Metode Systematic Layout Planning (SLP) dan Class Based Storage - Antonius Oksa Rizaldy Wiratama; Joko Susetyo*; Risma Adelina Simanjuntak (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
PT Solusi Cahaya Teknik is a company engaged in trading and maintenance service that sells consumable products for welding maintenance and repair. The material handling process cannot be separated from the facility layout in the company. The existing problem is regarding the layout that is not well ordered, causing longer and less optimal material handling. This study aims to propose a rearrangement of the facility layout by minimizing the material handling distance. The proposed facility layout is designed using the Systematic Layout Planning and Class Based Storage methods. The Systematic Layout Planning method is used to change the position of the department based on proximity, while Class Based Storage is used to rearrange the product storage area. The result of processing the material handling layout distance before repair is 16.273 meters. While the results of processing after the repair obtained the shortest material handling distance of 7.772 meters with a reduction rate of 8.501 m and a monthly material handling cost of Rp. 2,148,707.98 or 52.2% smaller than the pre-repair layout.